Immobilization of Horseradish Peroxidase onto Montmorillonite/Glucosamine–Chitosan Composite for Electrochemical Biosensing of Polyphenols - Piccoli, María Belén (2024)
Impact Factor: 4.9 (2023); 5-Year Impact Factor: 5.2 (2023).